The Application of Filanesia Basic Techniques on Football Playing Skills at SSB Pamong Praja Garut - Roby Hardian Susanto; Asep Angga Permadi; Ani Kurniawati (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objective. The purpose of this research is to apply the basic techniques of Indonesian soccer philosophy, namely attacking transition-defending, at SSB Pamong Praja Garut. Materials and Methods. The research employed an experiment with a one-group pre-test and post-test design, and was conducted at SSB Pamong Praja Tarogong Kidul Garut. The population consisted of 16 players, and the following instruments were used: First Touch test, passing test, dribbling test, heading test, shooting test, and soccer playing skills test (GPAI). SPSS version 26 was used for data processing. Results. The average values of the pre-test and post-test results are as follows: First Touch (pre-test 52.50 and post-test 69.38), Passing test (pre-test 218.13 and post-test 266.88), Dribbling test (pre-test 44.56 and post-test 52.69), Heading test (pre-test 49.50 and post-test 59.94), Shooting test (pre-test 81.88 and post-test 122.50), and soccer playing skills (0.3379-0.3857). Conclusion. Based on the analysis of data, it can be concluded that the application of the basic techniques of Indonesian soccer philosophy, namely attacking transition-defending, has a positive and significant influence on the improvement of the average values of the pre-test and post-test.